(untitled) (Journal of Plant Disease Sciences, 2017)
In India, pod blight (anthracnose) is considered the most severe soybean disease and observed in endemic ways (Chavan and Gupta, 2005). Yield losses of 30 to 50% were reported in Thailand and 100% in India (Sinclair 1989). Colletotrichum gliosporides, Collectortrichum truncatum Diaporthe , phaseolorum sojae Phomopsis f sp. , spp. are the prominent fungi that involved in pod blight complex. Stems, petioles, pods and seeds are all succunb to infection. Poor seed quality may leads of infection. If infected seeds are planted, emergence may be low due to seed rot or seedling blight. Pod blihght is seed-borne and seed-transmitted disease which might cause systemic infection (Neergard, 1979). Seed treatment with antagonists or fungicides protects the seed from infection by seed and soil borne pathogens (Ramos and Ribeiro, 1993). Foliar fungicides are also used to control numerous endemic diseases of soybean. Therefore, keeping the above points in view, the present investsigaton was carried to know the influence of seed dresser and the effect of foliar spray of fungicides applied at different growth period on pod blight severity and soybean grain yield.